A clinical observation of a Mycobacterium avium skin lesion in a patient with pulmonary tuberculosis - V. I. Mitrushkina; S. V. Smerdin; N. V. Stavitskaya; I. A. Lapyreva; S. V. Lazebny (State Scientific Center of Dermatovenereology and Cosmetology, 2020)
Mycobacterium tuberculosis and non-tuberculous mycobacteria (NTMB) are clinically distinct. Rapid detection and differentiation of M. tuberculosis complex (MTBC) and NTMB is critical for infection control. Due to the high prevalence of these diseases, the likelihood of co-infection is sufficiently high; however, information on the prevalence and occurrence of such combinations is extremely scarce. In this research, on the basis of a clinical case, an approach to developing a therapeutic strategy for cases of combined Mycobacterium avium and tuberculosis infections is presented.